1.7k views
1 vote
What’s the answer please

What’s the answer please-example-1

2 Answers

1 vote

Answer:


Explanation:


What’s the answer please-example-1
User Beau
by
5.4k points
6 votes

Answer:

(x, y ) = (5, 4 )

Explanation:

given the 2 equations

3x - 2y = 7 → (1)

- 3x + 5y = 5 → (2)

adding the 2 equations term by term will eliminate x

(3x - 3x) + (- 2y + 5y ) = (7 + 5 )

0 + 3y = 12

3y = 12 ( divide both sides by 3 )

y = 4

substitute y = 4 in either of the 2 equations and solve for x

(1 ) : 3x - 8 = 7 ( add 8 to both sides )

3x = 15 ( divide both sides by 3 )

x = 5

solution is (5 , 4 )


User Jnpdx
by
5.5k points